Comparison of the effect of quick response code-based training and traditional methods on the knowledge, skill, and satisfaction of the nursing students in using medical device - Masoumeh Bagheri-Nesami; Mahsa Kamali; Amirabbas Mollaei (Smart Learning Environments)
Abstract Nurses acknowledge that their understanding of the shortcomings in the utilization of medical devices stems from insufficient knowledge about their correct usage. The use of Quick Response (QR) technology has paved a new gateway for accessing information and resources. The available evidence confirmed the usefulness of QR codes for use in clinical settings as a tool for training. The present research performed a quasi-experimental research design to compare the effect of QR code-based training and traditional methods on the knowledge, skill, and satisfaction of the nursing students in using medical device. For the control group, textual Persian manuals, visual aids in the form of pictures, and URLs were available to the students. For the intervention group, the training approach based on QR codes was explained on the first day of their presence at the heart center. The knowledge, skill and satisfaction evaluations were conducted at the end of the clinical course on day 10. The group of nursing students who used the QR code-based training method had a statistically significant higher mean knowledge and skill score compared to the traditional training method group. The level of satisfaction among students who received training using QR codes was non-significantly higher than traditional method group. Nursing managers and educators can enhance the delivery of high-quality nursing care by using QR code.